Erytrodermia łuszczycowa po ogólnym zastosowaniu kortykosteroidów - opis przypadku - Joanna Maj; Alina Jankowska-Konsur; Karolina Kopeć; Anna Jagas (Termedia Publishing House, 2011)
Introduction. Erythroderma (exfoliative dermatitis) is an acute, generalizedinflammation of the skin, which affects at least 90% of its surface.It is a life threatening illness in the course of which various types anddegrees of scaling and itching are observed. The main causes of erythrodermaare psoriasis, atopic dermatitis, drug reactions, mycosis fungoidesand pityriasis rubra pilaris. Psoriatic erythroderma is classified as a secondary erythroderma. It may develop spontaneously or moreoften as a result of incorrect treatment.Objective. To present side effects of oral corticosteroids administrationin a patient with psoriasis.Case report. A 36-year-old woman, suffering from psoriasis for over7 years, was admitted to the hospital inMarch 2011 due to exacerbationof skin lesions up to erythroderma after administration of oral corticosteroidtherapy. Three weeks after corticosteroids withdrawal, significantworsening of the disease was observed. On admission she presentedmassiveskin inflammation, scaling and itching. Laboratory testsrevealed increased markers of inflammation. The patient was treatedwith combined immunosuppressive therapy and topical ointments.After 3 weeks, significant regression of skin lesions and normalizationof laboratory tests were observed.Conclusions. Psoriasis is a common cause of erythroderma in adults.Although in Europe the disease affects about 2% of the population andknowledge of its treatment should be common, cases of systemicadministration of corticosteroids in patients with psoriasis in the treatmentof the underlying disease or of the comorbidities are still beingreported.